2010
DOI: 10.1002/ibd.21255
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 inhibits migration of colonic lamina propria fibroblasts

Abstract: PGE2 reduced the migration of CLPF via elevation of intracellular cAMP. Potential mechanisms are changes in expression of cytoskeletal proteins, failure of CLPF to polarize, and a decreased amount of pMLC. This might be a possible reason for the impairment of intestinal wound healing in IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 42 publications
2
38
0
Order By: Relevance
“…Thus, the decrease in muscle migration by PPARc is most probably due to an increase in intracellular cAMP facilitated by PGE 2 . This is consistent with observations with other agents, such as bagonists, that increase intracellular cAMP and decrease airway [21] and vascular [22] smooth muscle cell and fibroblast migration [23]. It is likely that cAMP modulates the morphology of smooth muscle cells by inhibiting a Rac-dependent signalling pathway resulting in disassembly of actin stress fibres and lamellipodia, loss of focal adhesions and the formation of small F-actin rings [24], thus decreasing the ability of cells to migrate.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, the decrease in muscle migration by PPARc is most probably due to an increase in intracellular cAMP facilitated by PGE 2 . This is consistent with observations with other agents, such as bagonists, that increase intracellular cAMP and decrease airway [21] and vascular [22] smooth muscle cell and fibroblast migration [23]. It is likely that cAMP modulates the morphology of smooth muscle cells by inhibiting a Rac-dependent signalling pathway resulting in disassembly of actin stress fibres and lamellipodia, loss of focal adhesions and the formation of small F-actin rings [24], thus decreasing the ability of cells to migrate.…”
Section: Discussionsupporting
confidence: 77%
“…Studies on EP4 receptor knockout mice also suggested a protective role for PGE 2 against inflammation (Kabashima et al, 2002). On the other hand, PGE 2 may lead to impaired mucosal healing or excessive fibrosis by inhibiting the migration of the colonic lamia propria fibroblasts from patients with Crohn's disease (Rieder et al, 2010). PGE 2 production is increased in IBD (Baumeister et al, 1996), and it has been suggested as a mediator and/or prognostic marker in IBD (Wierciń ska-Drapalo et al, 1999;Sheibanie et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that a combination of ASCA, P-ANCA and anti-OmpC or a panel of antiglycan antibodies may aid in differentiation of CD from UC. In addition, the use of a panel of anticarbohydrate antibodies may provide additional help in distinguishing IBD from non-IBD disease patterns [27,35,47,48]. However, it should be noted that the presence of ASCA and P-ANCA does not mean the confirmation of the IBD diagnosis.…”
Section: The Role Of Serologic Markers In Ibd Diagnosismentioning
confidence: 99%
“…Antiglycan antibodies are useful in differentiation between CD and UC: patients with CD who are positive for at least one of the above-mentioned antiglycan antibodies could be differentiated from UC with approximately 80% sensitivity and more than 90% specificity [7,34,35,36]. …”
Section: Recently Characterized Serologic Ibd Markersmentioning
confidence: 99%